INCREASING EFFICIENCY DRAINING PRODUCTION OF CARANG MAS TELO WITH SPINNER INVERTER ON SMEs "NOVITA" IN BATU CITY, EAST JAVA - Siti Asmaul Mustaniroh (Journal of Innovation and Applied Technology, 2017)
Batu is an Agrowisata city, major producer of fruits and vegetables with the development of refined products based on local raw materials is Carang Mas Telo main raw materials used honey sweet potato.In Batu City, there is UKM “Novita”one that has developed innovations honey sweet potato into a carang mas telo, Production system problems faced by SMEs Cluster Carang Mas Telo include low production efficiency due to limited branch Telo mas production technology that is still manual (draining process) so that productivity can not be maximized. The new packaging can be done at least 24 hours to drain the oil conventionally using rice paper. The method of implementation of these activities is the integration of qualitative and quantitative descriptive form of mechanical technology transfer (Spinner Inverter .. The results demonstrate the transfer of technology implementation in the form of mechanical Spinner machine inverter can improve efficiency in working hours (work load becomes lighter 50%) and production costs ( the cost of labor usage reduced by 30%).